2013
DOI: 10.1002/ep.11843
|View full text |Cite
|
Sign up to set email alerts
|

Fate of tylosin a and its effect on anaerobic digestion using two tylosin inclusion methods

Abstract: This study examined the fate and effects of tylosin (TYL) on anaerobic digestion of swine wastewater at two concentrations of tylosin A (TYLA) using manure collected from swine fed with TYLA (TYL FED ) or direct addition of TYLA (TYL ADD ) to antibiotic-free swine manure, to examine whether there are differences between the two TYL addition methods on methane production and other fermentation parameters. TYLA and tylosin D (TYLD) concentrations, pH, Chemical oxygen demand (COD), Total nitrogen (TN), and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The diversity of antimicrobials detected in US swine manure includes the following: penicillin G, lincomycin, erythromycin, tylosin, bacitracin, sulfadimethoxine, sulfamethazine, sulfamethoxazole, chlortetracycline, oxytetracycline, and trimethoprim [16,[43][44][45][47][48][49]. This diversity is concerning as the complex mixture of antimicrobials in swine manure/lagoons may more readily lead to the development of multidrug-resistant pathogens.…”
Section: Swine Manurementioning
confidence: 99%
See 3 more Smart Citations
“…The diversity of antimicrobials detected in US swine manure includes the following: penicillin G, lincomycin, erythromycin, tylosin, bacitracin, sulfadimethoxine, sulfamethazine, sulfamethoxazole, chlortetracycline, oxytetracycline, and trimethoprim [16,[43][44][45][47][48][49]. This diversity is concerning as the complex mixture of antimicrobials in swine manure/lagoons may more readily lead to the development of multidrug-resistant pathogens.…”
Section: Swine Manurementioning
confidence: 99%
“…Metabolites of ampicillin [95], chlortetracycline [78], florfenicol [95], sulfadiazine [97], and tylosin [95] have been reported, reinforcing the contribution of biodegradation processes. Wang et al [45] found a lower reduction in methane production when tylosin A was added directly to manure before anaerobic digestion than when tylosin A was fed to animals, even when the influent tylosin concentrations to the digesters were identical. This difference was attributed to the presence of metabolites in the manure.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, this utilization of AFRs has been forbidden because it could cause serious environmental pollution and induce drug‐resistant bacteria to animals and human beings . AFRs were also used to produce energy through incineration and anaerobic digestion . However, high water content would decrease the efficiency of these processes.…”
Section: Introductionmentioning
confidence: 99%